5-HTTLPR genotype influences amygdala volume - Scherk, Harald (Steinkopff-Verlag, 2009)
BACKGROUND: Functional imaging studies in healthy individuals revealed an association between 5-HTTLPR genotype and neuronal activity in the amygdala. The aim of this study was firstly to investigate a possible overall impact of the 5-HTTLPR on amygdala volume in patients with bipolar disorder and healthy individuals and secondly to test a diagnosis specific influence of the 5-HTTLPR on amygdala volume. METHODS: We performed a region of interest analysis of amygdala volume in 37 patients with bipolar I disorder and 37 healthy control subjects. The 5-HTTLPR genotype of each proband was determined and the subjects were separated according to 5-HTTLPR genotype and for statistical analyses the groups SS and SL were combined and compared with the group LL. RESULTS: This study shows that carriers of the short allele (SL or SS) of the 5-HTTLPR polymorphism exhibit a relatively increased volume of the right amygdala compared to homozygous L-allele carriers irrespective of diagnosis status. However, further analyses with the factors genotype and diagnosis were not able to reproduce this result. CONCLUSIONS: The present findings are consistent with the view that the 5-HTTLPR polymorphism might modulate neuronal size or number in the amygdala. It would be worthwhile investigating the relationship between serotonin transporter function and amygdala function and volume in further studies.